Human resource management - Maimunah Aminuddin (Oxford revision series, 2009)
This is a comprehensive textbook for undergraduate and diploma students, including those who intend to specialize in this challenging and dynamic field and who hope to have a career as a human resource management specialist. This textbook is also essential reading for students who need an introductory paper in this area. It covers the range of human resource functions, including recruitment and selection, employee training, performance management of individual employees, systems for compensating and rewarding workers, development of systems to improve productivity in the organization, occupational safety and health, industrial relations and the right of employers to terminate the services of employees